Blue Resilience - Hossain, Peerzadi; Mudege, Netsayi; Kondowe, Jonah; Kakwasha, Keagan; Kuruganti, Praveen (2025)
Blue Resilience Generates and communicates climate information and advisory services to enable climate-informed decision-making at different scales — from small-scale fish farmers to policy makers — paving the way for climate risk management initiatives for aquatic foods in the SADC region.